Pengaruh Kompetensi Sumber Daya Manusia Terhadap Kinerja Karyawan Pada Koperasi TKBM Tebing Tinggi - Jumisar; Seno Aji (LPPM Universitas Adiwangsa Jambi, 2024)
At the Tebing Tinggi TKBM Cooperative, obstacles are always encountered in terms of the process of achieving performance. It needs to be understood that the performance expected from an employee is not easy because it is influenced by various factors such as competence, satisfaction, motivation, work environment and many other factors. Based on these factors, research was conducted with the title The Influence of Human Resource Competency on Employee Performance at the Tebing Tinggi TKBM Cooperative. This research aims to determine the effect of work competency on employee performance at the Tebing Tinggi TKBM Cooperative. Based on the results of the Significant Test, the t-count value is 3.183 with a significance level of 5%. Therefore, the tcount value is 3.183 > ttable 1.714 and the resulting significance value is 0.004 which is smaller than 0.05, so Ho is rejected and Ha is accepted. This means that the independent variable work competency (X) partially has a significant influence on employee performance (Y). The results of statistical tests show that the relationship between work competency and employee performance is positive (unidirectional). Based on the results of the t test, a significant value of 5% is obtained, so Ha is accepted or H0 is rejected. This means that work competency influences the performance of employees at the TKBM cooperative Tebing Tinggi.